IMPACT OF THERAPY ON HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS (ACCORDING TO THE RENAISSANCE REGISTER) - L. D. Vorobyeva; E. A. Aseeva; S. K. Solovyev; G. M. Koilubaeva; S. I. Glukhova (Научно-практическая ревматология, 2019)
Objective: to assess changes in health-related quality of life (HRQoL) in patients with systemic lupus erythematosus (SLE) during performed therapy.Subjects and methods. The investigation included 128 patients with reliable SLE who fulfilled the 2012 SLICC criteria. Sixty-eight patients received standard therapy; 60 used biological agents (BA). During the first visit and at 12 months, all the patients were assessed for disease activity using by SLEDAI-2K and for organ damage employing the SLICC damage index (DI). HRQoL was assessed by the LupusQoL questionnaire that was filled out by the patients independently.Results and discussion. At Visit 1, the disease activity index averaged 8.0±7.3 in the standard therapy group and 15.4±7.6 in the BA group (p≤0.001); DI was 1.2±0.9 and 1.8±1.8, respectively (p=0.008). BA-treated patients had significantly lower HRQoL scores on all questionnaire scales, except «dependence on others» and «emotional health» ones Both the standard therapy and BA groups showed significantly lower disease activity during Visit 2 at 12 months. HRQoL assessment revealed significant improvements in the scales «pain», «planning», «intimate relationships», «emotional health», «body image», and «fatigue» in the BA group. The standard therapy group had a statistically significant improvement in the scale «dependence on others». All the other scales of the questionnaire displayed a positive change in HRQoL; however, it did not reach statistical significance.